Evaluating the balance between vertical diffusive nitrate supply and nitrogen fixation with reference to nitrate uptake in the eastern subtropical North Atlantic Ocean. Issue 10 (22nd October 2013) - Painter, Stuart C.; Patey, Matthew D.; Forryan, Alexander; Torres‐Valdes, Sinhue
<x xml:space="preserve">Abstract</x> [1] The balance between N2 fixation and diffusive NO3− supply is a key determinant for assessing the importance of both processes for new production in subtropical waters. Here we report observations of integrated N2 fixation rates from the eastern subtropical North Atlantic Ocean with coincident estimates of diffusive NO3− supply. We find the average rate of N2 fixation is equivalent to 62% of the diffusive NO3− supply, though N2 fixation could exceed the diffusive flux at individual stations. Turbulent diffusivity measurements across the nitracline indicate a mean diffusivity of 0.077 cm2 s−1. If approximations for methodological underestimates in the dominant N2 fixation technique are considered, the magnitude of N2 fixation is shown to represent 100% of the NO3− flux on average, and can be almost threefold higher at individual stations. As the study site is characterized by low rates of N2 fixation compared to other sectors of the North Atlantic this confirms N2 fixation as a major source term across the subtropical North Atlantic. The seasonal context of our observations suggests environmental factors underlie the in situ variability in observed N2 fixation rates, and may well explain lower previous assessments of the importance of N2 fixation relative to diffusive NO3− supply in this region. The diffusive NO3− supply provides <20% of measurable NO3− uptake with the remainder supplied via other mechanisms, most notably nitrification. The mean integrated rate of N2 fixation equates to just 8% of the NO3− consumed on a daily basis by the phytoplankton community.